Cinema de animação: filmes e metáforas para crianças e adultos - Felipe de Castro Ramalho (2014)
The Survey "Animated Films: Movies and Metaphors for Children and Adults" is created to investigate the use of metaphors in animation and its representations and perceptions by different public. Five trajectories were highlighted to explain this goal. Firstly, through literature review , the metaphor is characterized and its application in language and in everyday life, focusing primarily on the concepts of the subject, addressed by the authors George Lakoff and Mark Johnson. Along with the identification of the metaphor and its application in film and subsequently the use of metaphors throughout the history of animation. Then is present the objective of this research, the analysis of the film narrative, the animated short film Night & Day (2010), from Pixar Animation Studios, with its possible implications to the use of metaphors. Stressing that the interpretation of metaphors in the short animated film is based on the study of metaphors from other authors. Furthermore, the explanation of the data collection process in regards to the reception study with children and adults, analysing in these groups the objective proposed for this work. Finally, the analysis and discussion of the research results with the perception of metaphors by the interviewees.